Affective Forecasting as a Resource for Situation Selection Across the Lifespan - Floerke, Victoria. (2017)
Abstract: The resources for situation selection, an emotion regulation (ER) strategy in which one chooses situations based on their emotional potential, remain unknown. Study 1 concerned whether affective forecasting, or the ability to predict how situations will make one feel, is associated with situation selection. Indeed, participants successful at forecasting their arousal during a stress test freely selected more negative relative to neutral situations. Study 2 was designed to replicate and extended this finding by comparing younger and older adults. Participants in Study 2 successful at arousal forecasting were less likely to choose positive relative to positive and neutral situations, and those more successful at positive forecasting were less likely to choose negative relative to negative and neutral situations. No age differences were found. Taken together, the results of these studies tepidly suggest that affective forecasting is a resource for situation selection that can be utilized similarly across the lifespan.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Psychology.; Advisor: Heather Urry.; Committee: Derek Isaacowitz, and Ayanna Thomas.; Keyword: Experimental psychology.